Reviewing Airport Privatization: An Experience of India - Mohan Phuyal (Publikasi Indonesia, 2023)
This study has reviewed the airport privatization scenario in the Indian context. It has examined the circumstances of airport infrastructure under the Public-Private Partnerships (PPPs) model. The Government of India (GoI) is justifying the development of airports through PPP mode due to their necessity to provide standard services and efficiency of the projects. However, the deficiency in investments and viability gap are being levy in the form of development. It has synthesized several works of literature. It looks at the historical changes and the ways that evidenced the changes. It has reviewed the developing scenario of airport PPP in India. During the 1990s economic liberation, the activities of PPPs emerged in the airport and aviation of India. India has 24 years history of airport PPPs. This study aims to provide a review of airport PPP experience in India. PPPs in the Indian airport industry are examined in sound regulation. The Government of India has adopted PPP schemes instead of going into full privatization of airports. Since the 2000s, PPP models have been adopted in the development of new airports and the reformation of operational and nonoperational airports. In the year 2006, Indira Gandhi International Airport, (IGIA) in Delhi, and Chhatrapati Shivaji International Airport (CSIA) in Mumbai were partially privatized. After the successful implication of PPPs, in the airport infrastructure the numbers are growing. In the year 2020, six airports were privatized through the PPP model by Adani Enterprises. To date, there are 21 airports in the pipeline of privatization.